Fluoroquinolones as enhancers of photocarcinogenesis: Proposed pathomechanisms - Ricardo Toipa Lopes; Margarida Gonçalo (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
Fluoroquinolones are photosensitizing drugs in humans, as they can enhance effects of ultraviolet A (UVA) radiation on the skin. UVA causes lesions both to deoxyribonucleic acid and other cellular organelles by Type I and Type II reactions (major and minor). The resulting photoproducts are highly reactive and can change the chemical composition of nucleotide bases, induce strand breaks and disrupt macromolecules and organelles. The cellular response can trigger apoptosis, causing a phototoxic skin reaction, recognized clinically as erythema, bullous or eczematous lesions, pseudoporphyria, onycholysis or subcorneal pustules. Moreover, cells with defects in oncogenes and/or tumor suppressor genes may be unable to promote apoptosis and thus give rise to a tumor cell. There has been growing evidence in the literature that photosensitizing drugs increase the photocarcinogenesis potential of UV radiation. In addition to being photocarcinogenic, UV radiation is immunosuppressive, which may explain why tumor cells multiply without control. The immunosuppression seems to be enhanced by fluoroquinolones. These drugs have proven to be photogenotoxic and photocarcinogenic in vitro and in animals. Clinical studies seem to suggest an increased risk of skin cancer in patients taking fluoroquinolones, with an even higher risk with longer courses of treatment. This article suggests a possible association between fluoroquinolones and skin cancer but also highlights a gap in the literature. Thus, it is important to increase preventive measures regarding sun exposure.